Human trafficking from the Islamic perspective - Mohd Nor, Aishah; Ab Hamid, Zuraini; Ramli, Lokman Effendi (Transnational Press London Ltd, 2024)
This study examines human trafficking from the Islamic perspective, exploring its fundamental principles, historical background, ethical considerations, and contemporary challenges. This study utilizes a qualitative approach which employs both doctrinal and socio-legal approaches. The doctrinal approach allows researchers to understand the Islamic principles of exploitation, while the socio-legal approach scrutinizes the application of Islamic rulings in society. The findings reveal the prohibition of seven types of exploitation, as emphasized in Islamic jurisprudence, which includes exploitation in slavery, transactions, labour, sexual activities, human organs, adoption and acts of injustice. Furthermore, this study explores the principle of non-punishment for victims and the types of punishment for the offender. This study emphasizes the need for collective action to combat exploitation, promote justice, and protect the rights and dignity of all individuals. It strongly encourages individuals, communities, religious leaders, policymakers, and international organizations to work together to eradicate exploitation, uphold justice, and safeguard every individual’s dignity and rights in alignment with Islamic principles and universal human values.